Renegotiation of Sales Contracts under Moral Hazard - Steven A. Matthews (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 1991)
Sales contracts emerge when a principal and an agent in amoral hazard environment cannot prevent themselves from renegotiating their contract. The renegotiation occurs after the agent chooses his unobservable effort, but before its consequences are realized. Unlike previous analyses, a contract is a single sharing rule of the classical variety, and the agent leads to renegotiation. A sales contract transfers the random return wholly to the agent, thereby relieving the principal of concern about his effort. Equilibria exist in which an initial sales contract is agree upon, but subsequently renegotiated to the (second-best) efficient contract. All equilibria satisfying a relatively weak refinement criterion are efficient in this sense; renegotiation does not reduce welfare. When the agent can finely control the probabilities of observable signals, the initial contract in every equilibrium satisfying the criterion must be a sales contract. Two applications are briefly considered, managerial compensation and the timing of new firms' security issues.
Keywords: D21; D82; C72; 330